N6-Methyladenosine and Viral Infection - Wei Dang; Wei Dang; Yan Xie; Yan Xie; Pengfei Cao; Shuyu Xin; Jia Wang; Jia Wang; Shen Li; Yanling Li; Jianhong Lu; Jianhong Lu (Frontiers in Microbiology, 2019)
N6-methyladenosine (m6A), as a dynamic posttranscriptional RNA modification, recently gave rise to the field of viral epitranscriptomics. The interaction between virus and host is affected by m6A. Multiple m6A-modified viral RNAs have been observed. The epitranscriptome of m6A in host cells are altered after viral infection. The expression of viral genes, the replication of virus and the generation of progeny virions are influenced by m6A modifications in viral RNAs during virus infection. Meanwhile, the decorations of m6A in host mRNAs can make viral infections more likely to happen or can enhance the resistance of host to virus infection. However, the mechanism of m6A regulation in viral infection and host immune response has not been thoroughly elucidated to date. With the development of sequencing-based biotechnologies, transcriptome-wide mapping of m6A in viruses has been achieved, laying the foundation for expanding its functions and corresponding mechanisms. In this report, we summarize the positive and negative effects of m6A in distinct viral infection. Given the increasingly important roles of m6A in diverse viruses, m6A represents a novel potential target for antiviral therapy.